Real Time Monitoring of N2O Emissions from Agricultural Soils using FTIR Spectroscopy. Issue 1 (30th January 2014) - Dubowski, Y.; Harush, D.; Shaviv, A.; Stone, L.; Linker, R.
Abstract : Emissions of N2 O from agricultural soils are an important source for this greenhouse gas. The present work examines the potential of Fourier transformed infrared (FTIR) spectroscopy coupled with a long path (LP) infrared (IR) gas cell for on‐line measurement of concentration and isotopic signature of N2 O emitted from soils. Nitrous Oxide was spectrally monitored during incubations of soil samples in a closed system under different conditions. Its emission from a Grumosol (Vertisol) was measured in presence and absence of acetylene, with various additions of nitrate and glucose, under aerobic and anaerobic conditions, and for two soil thickness layers. For comparison N2 O emissions from a Terra Rossa (Cambisol) and a Hamra (Luvisol) were measured in the presence and absence of acetylene. In an additional experimental set the isotopic signature of emitted N2 O was quantified after enrichment with K 15 NO3 . Acetylene addition led to an increase in N2 O emissions in all three soils but at various extents. Under aerobic conditions, N2 O emission from the Grumosol became detectable only when running the experiments with a thicker soil layer (10 mm), suggesting the existence of coupled nitrification–denitrification. Nitrate addition to soils enhanced N2 O emissions especially when coupled with glucose addition. Addition of 15 NO3 − to the Grumosol resulted in the emission of all four N2 O isotopologues: 14 N2 O, 15 N2 O, 14 N 15 NO, and 15 N 14 NO. The observed slight delay in appearance of the species containing 15 N and the relatively lower 15 N enrichment of the N2 O compared with the soil nitrate, indicate isotopic fractionation during denitrification. Yet, within the accuracy of our isotopic analysis, temporal emission patterns of 14 N 15 NO and 15 N 14 NO were similar indicating low possibility for "site preference" under the specific experimental conditions.